Tiaraoktavia11102001@gmail.com - Tiara Oktavia; Riski Seprianto; Maya Sintya; Elvira Nathalia Husna (Sahabat Publikasi, 2023)
This study aims to find out how to increase student concentration in learning Indonesian using the Example Non Example learning model at SD Negeri 56/I Aro. This type of research is classroom action research (PTK). The subjects of this study were 26 grade 1 students, the object of this research was an effort to increase the concentration of learning Indonesian according to learning, by using the Example Non Example learning model in class 1 SD Negeri 56/I Aro, the learning implementation was carried out through visiting activities this research instrument 1) Observation sheet 2) Test questions. From the results of data analysis, the Example Non Example learning model can improve learning outcomes in Indonesian language class 1 SD Negeri 56/I Aro. The increase in students who have completed learning from cycle I to cycle II is 8.24%. This can be seen from the acquisition of mastery learning outcomes of students in cycle I 71.76% of students who complete learning, cycle II 80% of participants who complete learning. Students who do not necessarily sound in cycle 2 will be given independent action in the form of exercises or remedial which are monitored by educators so that it is expected that all students can complete their studies.